Aspects on McCallin's paper - Helene Ekström (Grounded Theory Review: An International Journal, 2006)
I read Antoinette McCallin’s paper with interest and I have learned that there are problems which I have foreseen perhaps because I am, as many medical doctors are, unaware of the many “theories” or different perspectives that one can chose in undertaking a study. Kirsti Malterud, Professor of General Practice in Bergen, Norway, used to say that we are theoretically ignorant and instead focus on the pragmatic issues of how to survive the day and help the “sick” in an appropriate way. However, even if I feel like a real novice, I have some remarks about literature and grounded theory studies.